Qualitative text analysis a guide to methods, practice & using software - Kuckartz, Udo; McWhertor, Anne (Los Angeles, Calif. Sage, 2014)
Providing students and researchers with a guide to systematic analysis, with an emphasis on using software, this is a hands-on introduction to the central steps involved with qualitative analysis.
Analysing qualitative data-but how? -- The building blocks of systematic qualitative text analysis -- Basic concepts and the process of qualitative text analysis -- Three basic methods of qualitative text analysis -- Qualitative text analysis using computer assistance -- Quality standards, research report, and documentation.
"First published 2002."
Includes bibliographical references (pages 161-166) and index.
Translated from German by Anne McWhertor.
Keywords: Qualitative research -- Data processing; Social sciences -- Research -- Data processing